Local infusion of ghrelin into the lateral amygdala blocks extinction of conditioned taste aversion in rats. (1st January 2018) - Song, Ge; Zhu, Qianqian; Han, Fubing; Liu, Shuai; Zhao, Chenyang; Zhou, Yu
Highlights: Intra-LA infusion of ghrelin blocks extinction of acquired CTA memory. Intra-LA infusion of ghrelin blocks both extinction and acquisition through activation of the ghrelin receptor, GHS-R1a. PI3K inhibitor only abolishes the suppression of ghrelin/GHS-R1a signaling on acquisition, but not on extinction. Abstract: Ghrelin is an orexigenic brain-gut hormone promoting feeding and regulating energy metabolism in human and rodents. Our previous study showed that ghrelin locally infused into the lateral amygdala (LA) activates its receptor GHS-R1a and blocks acquisition of conditioned taste aversion (CTA) in rats. In this study, we further investigated the effect of ghrelin/GHS-R1a signaling on extinction of CTA. We found that local infusion of ghrelin (5 μM, 0.5 μl/side) into the LA not only interfered with CTA memory formation, but also the extinction of CTA memory. Pre-administration of GHS-R1a antagonist blocked ghrelin's effect on both CTA acquisition and extinction. However, pre-treatment with PI3K inhibitor only abolished the inhibitory effect of ghrelin on acquisition, but not on extinction. Altogether, our data indicated that ghrelin/GHS-R1a signaling in the LA circuit modulates both acquisition and extinction of CTA, the two forms of taste aversion processes with distinct mechanisms may also share certain molecular and circuit components in common.